Juxtacrine Activity of Estrogen Receptor α in Uterine Stromal Cells is Necessary for Estrogen-Induced Epithelial Cell Proliferation - Winuthayanon, Wipawee (Sci Rep, 2017)
Aberrant regulation of uterine cell growth can lead to endometrial cancer and infertility. To understand the molecular mechanisms of estrogen-induced uterine cell growth, we removed the estrogen receptor α (Esr1) from mouse uterine stromal cells, where the embryo is implanted during pregnancy. Without ESR1 in neighboring stroma cells, epithelial cells that line the inside of the uterus are unable to grow due to a lack of growth factors secreted from adjacent stromal cells. Moreover, loss of stromal ESR1 caused mice to deliver fewer pups due in part due to inability of some embryos to implant in the uterus, indicating that stromal ESR1 is crucial for uterine cell growth and pregnancy.